Breaking the cipher: ant eavesdropping on the variational trail pheromone of its termite prey - Wen, Xiao-Lan; Wen, Ping; Dahlsjö, Cecilia A L; Sillam-Dussès, David; Šobotník, Jan (Proceedings - Royal Society. Biological sciences, 2017)
Predators may eavesdrop on their prey using innate signals of varying nature. In regards to social prey, most of the prey signals are derived from social communication and may therefore be highly complex. The most efficient predators select signals that provide the highest benefits. Here, we showed the use of eusocial prey signals by the termite-raiding antOdontoponera transversaO. transversaselected the trail pheromone of termites as kairomone in several species of fungus-growing termites (Termitidae: Macrotermitinae:Odontotermes yunnanensis,Macrotermes yunnanensis,Ancistrotermes dimorphus). The most commonly predated termite,O. yunnanensis,was able to regulate the trail pheromone component ratios during its foraging activity. The ratio of the two trail pheromone compounds was correlated with the number of termites in the foraging party. (3Z)-Dodec-3-en-1-ol (DOE) was the dominant trail pheromone component in the initial foraging stages when fewer termites were present. Once a trail was established, (3Z,6Z)-dodeca-3,6-dien-1-ol (DDE) became the major recruitment component in the trail pheromone and enabled mass recruitment of nest-mates to the food source. Although the ants could perceive both components, they revealed stronger behavioural responses to the recruitment component, DDE, than to the common major component, DOE. In other words, the ants use the trail pheromone information as an indication of suitable prey abundance, and regulate their behavioural responses based on the changing trail pheromone component. The eavesdropping behaviour in ants therefore leads to an arms race between predator and prey where the species specific production of trail pheromones in termites is targeted by predatory ant species.
Keywords: zvířata; Formicidae; Animals; predátorské chování; feromony; Ants; Predatory Behavior; Pheromones; Isoptera